The Nature of Hope : Grassroots Organizing, Environmental Justice, and Political Change - Crane, Jeff; Miller, Char, 1951- (Book collections on Project MUSE., 2018)
"Examining the dynamics of environmental activism at the local level and how environmental and political cultures emerge in context of conflict. Considers how ordinary people coalesce to demand environmental justice and highlights the powerful role of intersectionality in shaping the on-the-ground dynamics of protest and social change"--